The Influence of Tax Sanction Avoidance and Taxpayer Income on Motor Vehicle Tax Compliance in Jakarta with Taxpayer Awareness as Moderation - Marilyn Marilyn; Herman Ruslim (PT. Publikasiku Academic Solution, 2023)
This study aims to examine the effect of tax sanctions avoidance and the amount of taxpayer income on the compliance of motor vehicle taxpayers in Jakarta with taxpayer awareness as moderation. The distribution of the Google form questionnaire (primary data) with the subject, namely motor vehicle taxpayers whose vehicles have Jakarta plates (plate B), and processed using Smart PLS by testing data validity using outer loading and data reliability using construct reliability and validity. The result obtained by this research by bootstrapping method is that the avoidance of tax sanctions has no effect. In contrast, the amount of taxpayer income and taxpayer awareness have a significant positive effect on motor vehicle taxpayer compliance, and taxpayer awareness does not moderate the effect of tax penalty avoidance and the amount of taxpayer income on motor vehicle taxpayer compliance. Submission of research to be input and information regarding the views of taxpayers regarding the compliance of motor vehicle taxpayers in Jakarta where the government can also continue to improve and develop facilities continue to be adequate and support taxpayers in carrying out their taxpayer compliance. This facility must also be effective and efficient so that taxpayers feel facilitated in carrying out their compliance.